A Semiotic Analysis of the Main Character’s Grief in the Film “The Goldfinch” on Netflix - Maha Anasya; Welly Wihayati (International Journal Labs, 2026)
The development of digital technology and the presence of streaming platforms such as Netflix have made films function not only as entertainment media but also as forms of mass communication that represent human emotional and social experiences. As an audiovisual medium, film contains various signs and symbols that construct certain meanings, including representations of loss and grief. John Crowley’s film The Goldfinch depicts the life of Theodore Decker after the loss of his mother in an explosion at an art museum. This study aims to analyze the representation of grief in the main character of The Goldfinch using Roland Barthes’s semiotic approach. This study uses a descriptive qualitative method, with data collected through film observation, in-depth interviews with three informants, and literature study. Data analysis was carried out using the interactive model of Miles and Huberman and was validated through source and theoretical triangulation. The results show that the representation of grief in the film is constructed through visual and symbolic signs, such as facial expressions, body language, dim lighting, room atmosphere, and the symbol of the painting The Goldfinch. At the denotative level, grief is shown through traumatic scenes, nightmares, and changes in the main character’s behavior. At the connotative level, these signs are interpreted as symbols of trauma, loneliness, and emotional isolation. Meanwhile, at the mythical level, the film constructs the view that loss is an emotional experience that can shape identity and have a long-term impact on one’s life. Thus, The Goldfinch represents grief as a complex emotional experience through visual and symbolic signs in the digital film medium.